Cambarus (Puncticambarus) callainus, a new species of crayfish (Decapoda: Cambaridae) from the Big Sandy River basin in Kentucky, Virginia, and West Virginia, USA - Thoma, Roger F.; Loughman, Zachary J.; Fetzner, James Jr. W. (Zootaxa, 2014)
Cambarus (Puncticambarus) callainus, new species, is a stream-dwelling crayfish endemic to the Big Sandy River basin in Kentucky, Virginia, and West Virginia. Within the basin, C. callainus occurs in the Levisa, Tug, and Russell fork watersheds. The new species is morphologically and genetically most similar to Cambarus veteranus, which is endemic to the Upper Guyandotte River basin of West Virginia. The new species can be differentiated from C. veteranus by its more lanceolate rostrum (width less than 50% length), slightly more obtuse suborbital angle, and less well-defined lateral impression at the base of the chelae.